Health Status, Disability and Retirement Incentives in Belgium - Alain Jousten; Mathieu Lefèbvre; Sergio Perelman (Institute for the Study of Labor (IZA), 2013)
Many Belgian retire well before the statutory retirement age. Numerous exit routes from the labor force can be identified: old-age pensions, conventional early retirement, disability insurance, and unemployment insurance are the most prominent ones. We analyze the retirement decision of Belgian workers adopting an option value framework, and pay special attention to the role of health status. We estimate probit models of retirement using data from SHARE. The results show that health and incentives matter in the decision to exit from the labor market. Based on these results, we simulate the effect of potential reforms on retirement.
Keywords: H55; J21; J26; J14; 330; unemployment; early retirement; disability; social security; pensions; labor force participation